(untitled) (Bangladesh Journal of Scientific Research, 2012)
Key words: Organic manures; growth; yield; nutrient uptake; maize DOI: http://dx.doi.org/10.3329/bjsr.v24i2.10770 Bangladesh J. Sci. Res. 24(2):135-144, 2011 (December)